Fractal Dimension Analysis and Earthquake Repeated Period Estimation in the Southern Part of Sumatra Subduction Zone (Bengkulu-Lampung-Sunda Segment) - Syamsurijal Rasimeng; Masdar Helmi; Tugiyono Tugiyono; Suharno Suharno (Geological Agency, 2022)
DOI:10.17014/ijog.9.3.383-394An earthquake seismicity parameter study has been conducted in the southern part of the Sumatra Subduction Zone (SSZ) for the period of 1919 to 2019 with a hypocentre depth of 120 km and magnitude of ≥4Mw. The researched area is divided into three segments, Bengkulu, Lampung, and Sunda segments, respectively. This study aims to evaluate the seismicity parameters in the form of a-value, b-value, fractal dimension, and probabilities of earthquake recurrence period. Frequency-magnitude correlation statistical approach introduced by Gutenberg-Richter was used to calculate the seismicity parameters based on catalogue data obtained from USGS. An a-value variation of 5.11±1.84 to 5.85±2.46 obtained indicates the most dominant seismic intensity. b-value of 0.69±0,.17 to 0.83±0.35 correlates with high-stress levels, the level of spatial heterogeneity on the SFZ, and the probabilities of bigger earthquakes in the future. The calculation of fractal dimension of 1.4±0.33 to 1.7±0.71 indicates an earthquake distribution pattern was caused by a single fracture zone along the southern part of SSZ. The fracture zone is located on the left and right sides of the southern part of SSZ, which may not have been connected. In addition, the calculation result of earthquake recurrence period with magnitude ≥6.5Mw indicates that there will be an 5 - 6 earthquake event in the Bengkulu segment, 2 - 3 event in the Lampung segment, and 1 - 2 event in the Sunda segment, while the probabilities of an earthquake with magnitude ≥7.5Mw along the southern part of SSZ is 1 - 2 times.